Recombinant Versus High-sensitivity Conventional Thromboplastin: A Randomized Clinical Study in Patients on Oral Anticoagulation - Finazzi, Guido; Falanga, Anna; Galli, Monica; Cortelazzo, Sergio; Remuzzi, Andrea; Barbui, Tiziano (Thrombosis and Haemostasis, 1994)
A prospective, randomized, double-blind clinical trial was carried out in a single center to compare the clinical and laboratory quality of oral anticoagulant therapy monitored with recombinant tissue factor (RTF) or with a sensitive, human-derived, conventional thromboplastin (CT) in the PT test. Seven hundred and fifty-seven consecutive patients receiving oral anticoagulation for various indications were randomized to RTF (n = 379) or CT (n = 368) for 6 months. Total follow-up was 167 and 153 patient-years for RTF and TP groups respectively. Fifty-six bleeding events were observed: 31 in the RTF group and 25 in the TP group. The incidence of bleeding was 18.5 and 16.5% pt-yrs for RTF and TP patients respectively (n.s.). The event-free follow-up curves were not significantly different between the two groups. The laboratory quality of oral anticoagulation was evaluated with the “last check in file” method: therapeutic INR was found in the same propor-tipn of RTF and TP patients (70.2% vs 68.8%). Our study shows that RTF is as effective as a sensitive, conventional thromboplastin for monitoring oral anticoagulation.